POMC and NPY mRNA expression during development is increased in rat offspring brain from mothers fed with a high fat diet - Klein, Marianne Orlandini; MacKay, Harry; Edwards, Alexander; Park, Su-Bin; Inhasz Kiss, Ana Carolina [UNESP]; Felicio, Luciano Freitas; Abizaid, Alfonso (Elsevier B.V., 2018)
Developmental programing is influenced by perinatal nutrition and it has long-lasting impacts on adult metabolism in the offspring. In particular, maternal high fat diet has been associated with increased risk of obesity and metabolic disorders during adulthood in the descendants. These effects may be due to the effects of the high fat diet on the development of the systems that regulate food intake and energy balance in the offspring hypothalamus. The arcuate nucleus (ARC) may be a particularly sensitive region to it as this nucleus contains the POMC and AgRP/NPY neurons that integrate the melanocortin system. Thus, the aim of this study was to investigate the effects of maternal high fat diet during pregnancy on the transcription factors that regulate hypothalamic development in the offspring as a potential mechanism that may result in altered neuronal expression of POMC, NPY and/or AgRP. To this end, pregnant females exposed to high fat diet (60% fat diet since day 0 of pregnancy) or standard rat chow were sacrificed on days 12, 14, 16 and 18 of gestation to obtain brains from their developing fetuses and examine the mRNA expression of transcription factors associated with the development of cells in the ARC. Results show that, while no changes in transcription factor expression between groups were observed, POMC and NPY mRNA expression were higher on embryonic day 18 in the high fat group. These results suggest that POMC and NPY expression are altered by in utero exposure to a high fat diet, but these changes in gene expression are not associated with changes in the expression of transcription factors known to determine the fate of ARC cells. (C) 2017 ISDN. Published by Elsevier Ltd. All rights reserved.
Keywords: Hypothalamic development; Metabolic programing; Food intake control; Offspring development; Obesity